TIME LEARNING MANAGEMENT NURSING STUDENTS USING TIME MANAGEMENT QUESTIONNAIRE (TMQ) IN IMPLEMENTING PROBLEM BASED LEARNING (PBL) METHODS - Richa Noprianty (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2019)
Background: The paradigm shift of learning method centered on the students has been applied to several universities, one of them by using Problem Based Learning (PBL) method. The importance of good time management will produce readiness to face the PBL process because in the PBL process using self directed learning where a student is required to be able to manage the time independently. The purpose of this study is to know the time management of nursing students by using Time Management Questionnaire (TMQ) in implementing Problem Based Learning (PBL) method in STIKes Dharma Husada Bandung.Method : The type of research is quantitative with the model of analytic design and cross sectional approach. The sample of research is student of class of 2014 and 2015 of Nursing Study Program of 169 students. The research instrument with Time Management Questionnare (TMQ) developed by Briton & Tesser (1991) has been tested its validity and reliability with Alpha Cronbach 0,800 by Allay & Kocak (2002). The questionnaire consists of short-term planning, attitude toward time and long-term planning.Result : Most respondents have good time management that is 53.3%. For short-term planning most have good time management of 58.6% with the highest mean of 4.25 on "Put the  priority first" points, the attitude towards time mostly has good time management of 61.5% with the highest mean of 4.10 at the point of "responsible for time for yourself", and long-term planning mostly has a good time management of 50.9% with the highest mean of 3.64 on points "if having a job, preferring installments in the task".Conclusion: There needs to be a re-review of the implementation of PBL method, especially on the weighting of self or group tasks so that students can make long-term planning that can review the learning process.